Pemanfaatan Media Permainan dalam Menstimulasi Perkembangan Berpikir Simbolik Anak Usia 4-5 Tahun - Mutmainah, Azkiah; Nugraha, Dadan; Syafri, Herman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Symbolic thinking is a crucial ability in the cognitive development of early childhood, particularly in the 4–5-year age range. At this stage, children begin to recognize and use symbols such as numbers and letters in their daily activities. This study aims to describe the role of play-based media in stimulating the development of symbolic thinking in early childhood. The research was conducted at RA ABC in Tasikmalaya City using a descriptive qualitative approach through observation of children's play activities, interviews with teachers, and documentation of the learning process. The research subjects consisted of 12 children from Group A and two classroom teachers. Data were analyzed using the interactive model of Miles and Huberman. The results show that play media designed in an engaging and developmentally appropriate manner can effectively facilitate the gradual understanding of symbols. The children not only recognized the forms of symbols but also began to associate them with meaning or function within the context of play. These findings support Piaget's concept of symbolic representation and expand its application in early childhood education settings. The novelty of this study lies in the design of the symbol media, which integrates elements of numeracy and literacy into a unified play experience. The implications of these findings highlight the importance of developing a play-based early childhood curriculum, providing innovative and accessible media for teachers, and enhancing teacher capacity in facilitating symbolic learning in a joyful and meaningful way